دور المكتبة الموسيقية في الوفاء بمتطلبات برنامج التربية الموسيقية بكلية التربية الأساسية بدولة الكويت - سيد علي، مها محمد عقيل (جامعة أسيوط - مركز تطوير التعليم الجامعي, 2015)
Based on the vision and mission of the college aiming at preparing a distinguished generation specialized in different musical arts and types, including oriental and classical arts to preserve Kuwaiti musical heritage by nationalistic cadres embodying the cultural history of Kuwait, and seeking to keep up with information technology and introduce it into specialized academician preparation programs to teach musical arts which are considered the language of the world whereby linguistic and geographical frontiers can be crossed so that it may become the language of the world, the present field study was conducted with the aim of shedding light on the importance of the presence of a specialized music library characterized by international standards in terms of content, programs, infrastructure and specialized human cadres. The study also presented examples of specialized historical music libraries in Arab and international countries. It was noticed that despite the music wealth and media they had, the majority of these music libraries, specially international historical libraries, were not independent from public libraries. The researcher used the descriptive method and designed a questionnaire to achieve the objectives of the study. The questionnaire was administered to 38 appointed and seconded faculty members teaching in the Dept. of Music Education. 76% of the subjects responded to the questionnaire. The researcher came up with the following results: - There should be a specialized technological music library that offer its services to faculty members, students, and other community members including specialists and academicians, and which is equipped with developed programs and technology in accordance with the specifications of international standards for specialized libraries. - As for the variable of gender, there are no statistically significant differences between the mean scores of males and females. - As for the variable of nationality, there are statistically significant differences in favor of non-Kuwaitis in the second axis of the study revolving around the contents of the specialized music library and the third axis dealing with the difficulties and obstacles facing the establishment of a specialized music library in the Department of Music Education. - As regards the variable of the academic degree and years of experience, there are no statistically significant differences in F-values at p = 0.05 for all the axes of the questionnaire.
انطلاقا من رؤية ورسالة الكلية لإعداد جيل متميز ومتخصص بالفنون الموسيقية وأنماطها المختلفة من شرقية وكلاسيكية لحفظ التراث الموسيقي الكويتي بكوادر وطنية تجسد تاريخ الكويت الحضاري، وسعيا لمواكبة تكنولوجيا المعلومات وإدخالها ضمن برامج إعداد المتخصصين الاكاديميين لتعليم أدب الفنون الموسيقية التي تعتبر لغة العالم التي بها تستطيع اختراق الحدود اللغوية والجغرافية لتصبح لغة العالم ولذلك تهدف هذه الدراسة الميدانية إلى إلقاء الضوء على أهمية وجد مكتبة موسيقية متخصصة تتميز معايير عالمية من حيث المحتويات والبرامج، والبنية التحتية، والكوادر البشرية المتخصصة. كما قدمت الدراسة نماذج من مكتبات موسيقية تاريخية متخصصة في البلاد العربية والعالمية وقد لوحظ أن المكتبات الموسيقية وبالرغم من مقتنياتها الموسيقى ووسائطها في أغلب النماذج ليست مستقلة عن المكتبات العامة خاصة العالمية التاريخية. استخدمت الدراسة المنهج الوصفي. وتم تصميم الاستبانة لتحقق أهداف الدراسة، وطبقت على عدد (٣٨) عضو هيئة تدريس ومنتدب للتدريس في قسم التربية الموسيقية. وبلغت النسبة المئوية للاستجابة ٧٦% وتوصلت الدراسة إلى ما يلي: - ضرورة وجود مكتبة موسيقية متخصصة تكنولوجية تقدم خدماتها لأعضاء هيئة التدريس والطلبة وفئات المجتمع من المتخصصين والأكاديميين وذوي الاحتياجات الخاصة وتزود بالبرامج والتقنيات المتطورة طبقًا لمواصفات المعايير العالمية للمكتبات المتخصصة. بالنسبة لمتغير النوع والجنسية: - لا توجد فروق ذات دلاله احصائية للفروق بين المتوسطات الحسابية لمتغير النوع. - توجد فروق ذات دلالة إحصائية بالنسبة لمتغير الجنسية لصالح الغير كويتي. بالنسبة لمتغير الدرجة العلمية- وسنوات الخبرة: - لا توجد فروق ذات دلالة إحصائية لقيم (ف) عن مستوى (0.05) لجميع محاور الاستبانة للدرجة العلمية- وسنوات الخبرة وهي غير دالة إحصائيا.
Keywords: البرامج التربوية -- المكتبة الموسيقية -- التربية الموسيقية -- طلاب الجامعات -- كلية التربية الأساسية -- الكويت